- Eocene initiation of Ross Sea dextral seismogenic faulting and implications for East Antarctic neotectonics - ROSSETTI, FEDERICO; F. STORTI; MARTINA BUSETTI; F. LISKER; GIANFRANCO DI VINCENZO; ANDREAS LUFER; SERGIO ROCCHI; SALVINI, Francesco (2006)
The Ross Sea region of the East Antarctic plate provides evidence for intraplate tectonic activity in Cenozoic times. Still unresolved are the cause, timing and kinematics of this intraplate tectonism. By integrating and discussing the different (kinematic and temporal) signals of Cenozoic tectonism, intraplate dextral shearing is recognized as the main tectonic regime controlling the structural architecture of the Ross Sea region from the Mid-Eocene (c. 40–50 Ma) onward. We speculate that propagation and persistence of this tectonic regime through time constitutes a feasible seismogenetic framework to explain past and current tectonism in the Ross Sea region.